Inflation scares and forecast-based monetary policy - Athanasios Orphanides; John C. Williams (Federal Reserve Bank of Atlanta, 2003)
Central banks pay close attention to inflation expectations. In standard models, however, inflation expectations are tied down by the assumption of rational expectations and should be of little independent interest to policy makers. In this paper, the authors relax the assumption of rational expectations with perfect knowledge and reexamine the role of inflation expectations in the economy and in the conduct of monetary policy. Agents are assumed to have imperfect knowledge of the precise structure of the economy and the policymakers' preferences. Expectations are governed by a perpetual learning technology. With learning, disturbances can give rise to endogenous inflation scares, that is, significant and persistent deviations of inflation expectations from those implied by rational expectations. The presence of learning increases the sensitivity of inflation expectations and the term structure of interest rates to economic shocks, in line with the empirical evidence. The authors also explore the role of private inflation expectations for the conduct of efficient monetary policy. Under rational expectations, inflation expectations equal a linear combination of macroeconomic variables and as such provide no additional information to the policy maker. In contrast, under learning, private inflation expectations follow a time-varying process and provide useful information for the conduct of monetary policy.
Keywords: 330; Equilibrium (Economics); Monetary policy; Macroeconomics; Inflation (Finance); Forecasting